Investigating continuation of folic acid supplementation during peri-conceptional period: a community-based cross-sectional study - Yanyan Mao; Hong Hu; Dongyan Chen; Yuhang Fang; Jun Liu; Min Li; Weijin Zhou (BMC, 2023)
Abstract Background Maternal folate may not reach an optimal level to prevent neural tube defects if supplementation commenced post-conception or took place pre-conception only. Our study aimed to investigate the continuation of folic acid (FA) supplementation from pre-conception to post-conception during peri-conceptional period and to examine its differences in FA supplementation between the subgroups taking the initiation timing into consideration. Methods This study was conducted in two community health service centers in Jing-an District of Shanghai. Women accompanying their children to pediatric health clinics of the centers were recruited and asked to recall information concerning their socioeconomic and previous obstetric characteristics, utilization of healthcare and FA supplementation before and/or during pregnancy. The continuation of FA supplementation during peri-conceptional period were categorized into three subgroups: Supplementing with FA pre- and post-conception; supplementing with FA preconception only or post-conception only; no FA supplements pre-conception and post-conception. The relationship between FA continuation and couples' characteristics were examined as setting the first subgroup as the base reference. Results Three hundred and ninety-six women were recruited. Over 40% of the women started FA supplementation after conception and 30.3% of them supplemented with FA from pre-conception to the first trimester of their pregnancy. Compared to this one-third of participants, women who didn't supplemented with any FA during peri-conceptional period were more likely to have no utilization of pre-conception healthcare ( $$OR$$ OR = 2.47, 95% $$CI$$ CI : 1.33-4.61) or antenatal care ( $$OR$$ OR = 4.05, 95% $$CI$$ CI : 1.76-9.34), or who had a lower family socioeconomic status ( $$OR$$ OR = 4.36, 95% $$CI$$ CI : 1.79-10.64). Women who supplemented with FA pre-conception only or post-conception only were more likely to have no utilization of pre-conception healthcare ( $$OR$$ OR = 2.94, 95% $$CI$$ CI : 1.79-4.82), or to have no previous pregnancy complication ( $$OR$$ OR =1.80, 95% $$CI$$ CI : 0.99-3.28). Conclusion Over two-fifth of the women started FA supplementation and only one-third of them had an optimal supplementation from pre-conception to the first trimester. Maternal utilization of healthcare before or during pregnancy together with maternal and paternal socioeconomic status may play a role in the continuation to FA supplementation pre- and post-conception.